An entanglement of people-things: Place-Hampi. (25th November 2008) - Kenderdine, Sarah
Drawing upon Interpretive Archaeology, Interpretive Archaeological Systems theory and Symmetrical Archaeology, this discussion examines several philosophical considerations (phenomenology, embodiment, corpothetics and mediation) which form powerful interlocking arguments, whose qualities are prerequisites for building presence and place in virtual heritage landscapes. Through the two interactive display systems (Place and the Advanced Visualization Interactive Environment) a translation of spatial potential is enacted in Place-Hampi where participants are able to transform myths into the drama of a co-evolutionary narrative by their actions within the virtual landscape and through the creation of a virtual heritage embodiment of a real world dynamic.